PENGARUH EDUKASI GIZI TENTANG UPAYA PENCEGAHAN OBESITAS DENGAN MEDIA TIKTOK DAN POSTER TERHADAP PENGETAHUAN DAN SIKAP REMAJA DI SMA NEGERI 66 JAKARTA - Putri Hapsari Althoofany, (2022)
The high prevalence of obesity in teenager with an age range of 16-18 years which continues to increase from year to year is still a nutritional problem in Indonesia. Lack of knowledge of teenager about the incidence of obesity is one of the factors that cause obesity. Nutrition education is the right solution in increasing knowledge and attitudes about obesity in adolescents. Tiktok and posters that are currently developing are the right media to use in education. This study aims to determine the effect of nutrition education on efforts to prevent obesity by using Tiktok and posters on the knowledge and attitudes of teenager at SMA Negeri 66 Jakarta. This study uses a quasi experimental research method without group controls, with a two group pretest-posttest design. A total of 62 students in class X were divided into 2 groups, namely the Tiktok and poster groups. Statistical tests used were Wilcoxon and Mann-Whitney test. The results showed that there was an effect of nutrition education using Tiktok and posters on increasing knowledge with a p-value of 0.000. While attitudes on Tiktok media have the effect of nutrition education with a p-value of 0.046 and on poster media there is no significant effect with a p-value of 0.157. The results of the analysis show that Tiktok media is considered more effective and has an impact on the knowledge and attitudes of teenagers at SMA Negeri 66 Jakarta compared to poster media.